Notes on the genus Sakakibarella Creão-Duarte with description of three new species (Membracidae: Membracinae: Hoplophorionini) - Camacho, Luis F.; Flórez-V, Camilo; Evangelista, Olivia (Zootaxa, 2017)
Three new species of Sakakibarella Creão-Duarte are described from Colombia: S. albinoi Flórez-V and Camacho sp. nov., S. crassa Flórez-V and Camacho sp. nov., and S. santaceciliae Flórez-V and Camacho sp. nov. The taxonomic identity of the genus with regard to other taxa in the tribe is discussed. A key to species of Sakakibarella is presented, as well as illustrations of the holotypes of six of the seven species currently recognized in the genus. Remarks concerning the biology of the new species are also provided.